2017
DOI: 10.1111/den.12825
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological analysis of cold snare polypectomy and its indication for colorectal polyps 10–14 mm in diameter

Abstract: CSP is a safe procedure for polyps 2-14 mm. However, CSP has limitations in terms of the histopathological margin and loss of muscularis mucosa in specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 25 publications
1
60
0
Order By: Relevance
“…16 Biopsy from mucosal defect or CSDP contained muscularis mucosa in 38% in our study. Because, complete removal of the entire mucosal layer is important to avoid recurrence after CSP for small cancers invading the muscularis mucosa, which can be completely removed with endoscopic mucosal resection following submucosal injection.…”
Section: Discussionmentioning
confidence: 54%
“…16 Biopsy from mucosal defect or CSDP contained muscularis mucosa in 38% in our study. Because, complete removal of the entire mucosal layer is important to avoid recurrence after CSP for small cancers invading the muscularis mucosa, which can be completely removed with endoscopic mucosal resection following submucosal injection.…”
Section: Discussionmentioning
confidence: 54%
“…We think this trend should be changed in the future. In addition, some studies have shown that CP is useful for removing polyps of more than 10 mm in size [22-24]; however, some of those reports recommend piecemeal polypectomy. The reported rate of incomplete resection by CP was 3.9% [25] and there is a report of recurrence after CP [26]; thus, careful consideration for the indication of size is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 126 lesions were removed using CSP, but there was no adverse event [27]. In histological analysis of colorectal polyps removed by CSP, the muscularis mucosae were not resected in 27.8% of patients [28]. Thus, further studies are needed to evaluate the effectiveness of CSP for small SNADETs, especially regarding the lesion residue and recurrence.…”
Section: Characteristics and Treatment Outcome Of Each Er Methodsmentioning
confidence: 99%